Theoretical and Methodological Enhancement of Managerial Activity in the Teachers’ Professional Motivation Formation of Future Specialists - Anesova, Albina Zhenisovna; Akhmejanov, Assad Bisengazievich; Toleubekova, Rymshash Kameshovna; Zhumataeva, Engilika (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
This article is devoted to the problem of the enhancement of the managerial competence required by rectors of higher education institutions in the Republic of Kazakhstan. The essence of this competence reveals, by its component composition (the strategic, communicative, organizational, psychological, pedagogical, entrepreneurial, and political sub-competencies) is determined and justified. As a practical mechanism for the managerial competence enhancement, it proposes to use the profession-oriented educational technology based on the humanistic and competence-based approaches within the framework of the stochastic scientific paradigm. It notes that this educational technology complies with the modern philosophy of education called “lifelong learning”.